Porfirinas de bismuto e antimônio: obtenção, avaliação da atividade leishmanicida e investigação dos possíveis mecanismos de ação - Marcela Luisa Gomes (2016)
Bismuth and antimony compounds have wide application in medicine, mainly for the treatment of gastric diseases and leishmaniasis, respectively. We describe at this work the syntheses and characterization of new Sb(V) e Bi(III) complexes derived from the following second generation porphyrins: 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin (H2T4MPP); 5,10,15,20-tetrakis(3,5-dimethoxyphenyl)porphyrin (H2T3,5DMPP); 5-(4-aminophenyl)-10,15,20-trisphenylporphyrin (H2APTPP); 5-(4-nitrophenyl)-10,15,20-trifenilporphyrin (H2NPTPP); 5,10-bis(4-aminophenyl)-15,20-diphenylporphyrin (cis-H2DAPDPP) e da 5,15-bis(4-aminophenyl)-10,20-diphenylporphyrin (trans-H2DAPDPP); 5,10-bis(4-nitrophenyl)-15,20-diphenylporphyrin (cis-H2DNPDPP) e da 5,15-bis(4-nitrophenyl)-10,20-diphenylporphyrin (trans-H2DNPDPP).The compounds were characterized by elemental analysis (CHN), spectroscopic absorption in the ultraviolet/visible region (UV-vis and nuclear magnetic resonance of hydrogen (1H NMR) and mass spectrometry. Due to the wide applicability of antimony and bismuth compounds in medicine, the activity of these complexes was verified against Leishmania parasites. Initially, the compounds were tested against Leishmania promastigotes. The [Sb(V)Br2(T4CMPP)]Br (IC50 = 1.23 molL-1, obtained during the Masters) and [Sb(V)BrCl(T4MPP)]Br (IC50 = 0.2molL-1 ) complexes were the most active and then they were also tested against the intracellular amastigotes. The [Sb(V)Br2(T4CMPP)]Br complex showed 50% reduction in infection index at 72.8 ± 1.3 mol for resistant strains and 53.0 ± 1.2 mol L-1 to sensitive. Surprisingly, the complex was much more active than conventional drug, the glucantime®. The [Sb(V)BrCl(T4MPP)]Br complex showed IC50 = 0.07 mol L-1, that is, smaller than the other values for promastigotes. The possible action mechanisms were also investigated, as the ergosterol biosynthesis inhibition and DNA interactions. For parasites treated with [Sb(V)Br2(T4CMPP)]Br and [Sb(V)BrCl(T4MPP)]Br compounds, a significant level ergosterol reduction was observed, thus inferring that this may be the action mechanism of these complexes. In addition, the studied complexes have high ability to interact with DNA, with constants (Kb) at 105order. In parasites treated with the compounds [Sb(V)Br2(T4CMPP)]Br and [Sb(V)BrCl(T4MPP)] Br, there was significant reduction of ergosterol levels, inferring that this may be the action mechanism of these complexes. Therefore, these two compound appear as potential antileishmanial drugs candidates and its action mechanism may be ergosterol biosynthesis inhibition.